Risk and Benefit Analysis of Unsecured and Non-Contractual Lending Practices in the KOBATEKSI Cooperative: A Legal and Economic Perspective - M. Ja'far Sodiq Maksum; M. Farid Nasrulloh (LPPM Universitas KH. A. Wahab Hasbullah, 2025)
This study examines the practice of providing unsecured loans without written agreements at KOBATEKSI Cooperative, which operates based on social solidarity in Jombang. The research highlights the tension between social values, legal certainty, and financial risk management. Internal data and interviews indicate high economic risk (NPL increased from 14% to 27% between 2022–2024) and legal risk due to the absence of formal contracts. Findings suggest that trust-based strategies are effective in small communities but insufficient as the cooperative expands. The study recommends governance reforms through simple written agreements, risk-based loan SOPs, enhanced legal and financial literacy for members, and internal mediation mechanisms. This approach aims to balance social inclusion principles with legal certainty to ensure cooperative sustainability.